PERAN FINANCIAL TECHNOLOGY DALAM MANAJEMEN KEUANGAN - Agustian, Aldy; Aidah, Risa Nur; Ridwan, Rizky; Rachmanda, Yudi Setia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT The rapid advancement of Financial Technology (FinTech) has introduced innovations in digital financial services such as electronic wallets, peer-to-peer lending, and investment applications. This transformation creates opportunities to improve transaction efficiency, cash flow management, and financial transparency. However, its adoption in Indonesia still faces challenges, including low digital financial literacy, limited infrastructure, data security issues, and incomplete regulations. These conditions highlight a research gap regarding the contribution of FinTech to the effectiveness of financial management, particularly for individuals and MSMEs. This study employs a scoping review method based on the Arksey and O’Malley framework, which includes five stages: identifying research questions, searching for relevant studies, selecting articles, analyzing data, and compiling the report. Of the 854 articles identified, 12 met the inclusion criteria for further analysis. The analysis focuses on the role of FinTech in financial management, the challenges faced, and the factors influencing its success. The findings show that FinTech significantly contributes to expanding access to financial services, improving literacy, and enhancing the effectiveness of financial management for both individuals and MSMEs. Digital features such as real-time transaction recording, automatic payment reminders, and capital access through P2P lending have been shown to increase efficiency and transparency. However, low digital literacy, technological disparities, and issues of security and regulation remain major obstacles. FinTech holds great potential to support financial inclusion and management effectiveness; therefore, synergy between technological innovation, enhanced digital literacy, and adaptive regulation is needed to create an inclusive and sustainable digital financial ecosystem. ABSTRAK Kemajuan pesat Financial Technology (FinTech) telah menghadirkan inovasi dalam layanan keuangan digital seperti dompet elektronik, peer-to-peer lending, dan aplikasi investasi. Transformasi ini membuka peluang peningkatan efisiensi transaksi, pengelolaan arus kas, dan transparansi keuangan. Namun, pemanfaatannya di Indonesia masih menghadapi kendala berupa rendahnya literasi keuangan digital, keterbatasan infrastruktur, keamanan data, dan regulasi yang belum komprehensif. Kondisi ini menimbulkan kesenjangan penelitian terkait kontribusi FinTech terhadap efektivitas manajemen keuangan, khususnya bagi individu dan UMKM. Penelitian ini menggunakan metode scoping review dengan mengacu pada kerangka Arksey dan O’Malley yang meliputi lima tahap: identifikasi pertanyaan penelitian, penelusuran studi relevan, seleksi artikel, analisis data, dan penyusunan laporan. Dari 854 artikel yang ditemukan, 12 memenuhi kriteria inklusi untuk dianalisis lebih lanjut. Analisis difokuskan pada peran FinTech dalam manajemen keuangan, tantangan yang dihadapi, serta faktor-faktor yang memengaruhi keberhasilannya. Hasil penelitian menunjukkan bahwa FinTech berkontribusi signifikan dalam memperluas akses layanan keuangan, meningkatkan literasi, dan mendorong efektivitas pengelolaan keuangan pribadi maupun UMKM. Fitur digital seperti pencatatan transaksi real-time, pengingat pembayaran otomatis, dan akses modal melalui P2P lending meningkatkan efisiensi dan transparansi. Namun, rendahnya literasi digital, kesenjangan teknologi, serta isu keamanan dan regulasi masih menjadi hambatan utama. FinTech berpotensi besar mendukung inklusi dan efektivitas manajemen keuangan, sehingga diperlukan sinergi antara inovasi teknologi, peningkatan literasi digital, dan regulasi adaptif untuk menciptakan ekosistem keuangan digital yang inklusif dan berkelanjutan.